2022
DOI: 10.1186/s12984-022-01059-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of external and internal focus of attention on visual dependence and EEG alpha oscillations during postural control

Abstract: Background The ability to maintain upright posture requires successful integration of multiple sensory inputs (visual, vestibular, and somatosensory). When one or more sensory systems become unreliable, the postural control system must “down-weight” (or reduce the influence of) those senses and rely on other senses to maintain postural stability. As individuals age, their ability to successfully reweight sensory inputs diminishes, leading to increased fall risk. The present study investigates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The increased alpha power may reflect either impaired central processing of visual cues, or difficulties resolving visual cues from conflicting somatosensory cues. Previous research has shown increased alpha power when the inputs from the visual and somatosensory systems are incongruent in healthy adults 19 . Theta/beta ratio power increased in participants with PD when relying on somatosensory cues 42 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The increased alpha power may reflect either impaired central processing of visual cues, or difficulties resolving visual cues from conflicting somatosensory cues. Previous research has shown increased alpha power when the inputs from the visual and somatosensory systems are incongruent in healthy adults 19 . Theta/beta ratio power increased in participants with PD when relying on somatosensory cues 42 .…”
Section: Discussionmentioning
confidence: 91%
“…Changes in occipital alpha power appear to reflect the sensory and movement-related information processing of postural control 18 . In neurotypical young adults, occipital alpha power increased when standing with the eyes closed 19,20 . Theta/beta ratio power reflects cognitive activity related to attention and working memory processes 21,22 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, based on our results we recommend future research to investigate whether IMC is affected by CMP within the beta band, looking specifically at the SOL-GM and PL-SOL muscle pairs, given that we observed largest effects for these frequencies and muscle pairs (see supplementary data 1). Furthermore, recent work has shown that CMP can alter sensory processing and integration during standing balance tasks (Ma et al, 2022). Future work may explore how IMC is affected by, for instance, multisensory conflict during balance, and what role CMP plays in aggravating or resolving such conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…Following the data decomposition by ICA, we used the ICLabel function in the EEGLab (Delorme & Makeig, 2004) to identify artifactual independent components (Pion-Tonachini et al, 2019). The thresholds of independent components were determined based on previous research (Ma et al, 2022). To ensure reproducibility and to avoid subjective bias, over 80% of artifactual independent components were removed.…”
Section: Eeg Data Processing and Analysismentioning
confidence: 99%